Performansi Throughput Jaringan 4G Pada Lantai 2 Blok 6 Kampus PCR: Performansi Throughput Jaringan 4G Pada Lantai 2 Blok 6 Kampus PCR - Harpawi, Noptin; Yuli Triyani (Politeknik Caltex Riau, 2024)
Nowadays, 4G cellular service has become a basic need especially for campus communities. Information exchange and learning processes often utilize technology in this service. Block 6, floor 2 of the PCR campus consists of 2 lecturer rooms, 4 laboratories, 1 meeting room and 1 research room. Of course, this is one of the spots in PCR where 4G service is needed. Of the several 4G service providers in Indonesia, Telkomsel is the operator that has the most customers. 4G network performance can be seen in several parameters such as RSRP, RSRQ, CSFB, Throughput and SINR. These parameters are obtained through a process called Drive Test (DT). Drive Tests carried out by walking in closed areas such as inside buildings, malls, and such are called Walktests (Indoor Drive Tests). This research is focused on observing only one parameter, namely throughput. From this research, the maximum throughput value for Telkomsel's 4G network in Block 6, Floor 2, PCR Campus at the time of measurement (July 13 2023 at 16.43 WIB) was 2.18 Mbps. So when compared with the KPI set by Telkomsel, the throughput value in block 6, floor 2 of the PCR campus is in the